Effect of Chewing Hardness on Cognitive-Associated Brain Regions Activation - Hansol Lee; Ji-Hye Kim; Seungho Kim; Sung Ho Jang; Yongmin Chang; Youn-Hee Choi (International Dental Journal)
Introduction and aims: Recent findings suggest a potential correlation between mastication and cognitive processes. However, the comprehensive investigation into the neurobiological mechanisms of masticatory control, such as the impact of chewing hardness, on cognitive function, remains incomplete. This study aims to investigate the impact of chewing hardness, as an aspect of masticatory control, on cognitive function by examining brain activation patterns during hard and soft chewing conditions. Methods: A total of 52 healthy young adults (average age of 21.81 years; 24 men and 28 women) underwent fMRI scanning, during which 27 individuals chewed soft and 25 individual chewed hard material. The functional magnetic resonance imaging (fMRI) was employed to elucidate the overlapping and distinct patterns of activated brain regions associated with soft- and hard-chewing conditions. Subsequently, correlations between these activated brain regions and neuropsychological measures were assessed. Results: Conjunction analysis revealed that both soft- and hard-chewing conditions stimulated brain regions directly associated with orofacial movement and spatial information processing. Two-sample t-test result indicated that the hard-chewing group had higher activation mostly in the caudate nucleus and frontal brain regions associated with cognitive function compared with the soft-chewing group. Furthermore, the activation strength of these brain regions positively correlated with neuropsychological measures. Conclusion: The findings suggest that hard-chewing may be more effective than soft-chewing in stimulating cognition-associated brain regions, potentially enhancing cognitive processing. Clinical relevance: Our study shows that hard-chewing activates brain regions linked to cognitive function more than soft-chewing. This suggests that harder chewing could be used as a simple, non-invasive method to enhance cognitive processing. Incorporating harder foods into the diet may offer a practical approach to support cognitive health and improve mental performance.